MANAGING INDIA the idea of the iims and its changing contexts. - Babu, R. Rajesh; Thakur, Manish (ROUTLEDGE INDIA, 2024)
This book explores the history and metamorphosis of the Indian Institutes of Management (IIMs), the premier business and management schools in India, and their significance within the changing landscape of higher education, nation-building and socio-economic development in the country. Over the past decades, IIMs, as institutions, have recalibrated their goals and priorities to address contemporary challenges in a globalised world, changing aspirations of a rapidly growing population and the changing idea of India. This book examines different facets of the challenges the institutes have faced in the aftermath of independence. These include the challenges of effective institutional governance; ensuring equity and access; democratisation; raising the bar for teaching and research; addressing national imparities and global benchmarking; accreditation and ranking; and academia, industry, and employability. Drawing upon the interplay of the experiential and analytical, the contributors to the volume also engage with the Indian knowledge system and the contested terrain of global theory and research. This volume will be of interest to scholars, researchers and practitioners of education, management studies, academic administration, and policymaking in the field of higher education.
Keywords: Indian Institute of Management Studies.; Management -- Study and teaching -- India.; elektronické knihy; electronic books